Exploring personal aptitudes and personality traits that, together with social determinants, shape health behaviors and conduct: a thematic analysis based on the Capability, Opportunity, Motivation and Behavior (COM-B) change system - Young-Silva, Yudy; Berenguera, Anna; Juvinyà-Canal, Dolors; Martí-Lluch, Ruth; Arroyo-Uriarte, Paula; Tamayo-Morales, Olaya; Marcilla-Toribio, Irene; Elizondo-Alzola, Usue; Méndez-López, Fátima; Chela-Àlvarez, Xènia; Motrico, Emma (Frontiers in Public Health, 2024)
Introduction Effective implementation of strategies to promote health and prevent noncommunicable illnesses requires a profound understanding of the interaction between the individual and society. This study brings to health research the consideration of psychosocial factors that influence the maintenance and change of health behaviors and conduct. From a primary care perspective, it is crucial to propose a biopsychosocial approach for the development of health promotion and self-care programs that embrace personal aptitudes as a relevant individual aspect. Objectives To explore experiences related to personal aptitudes and personality traits that influence health behaviors and conduct, taking into account the social determinants of health, through a thematic analysis based on the capability-opportunity-motivation and behavior (COM-B) system. Methods and analysis This qualitative research is carried out from a descriptive phenomenological perspective, based on 17 focus groups in which 156 people participated. Inductive and deductive analysis techniques were used following Lincoln and Guba’s criteria of methodological rigor. In addition to 7 different triangulations of analysts, 6 main categories were identified based on the COM-B system: psychological capacity, physical capacity, physical opportunity, social opportunity, reflective motivation, and automatic motivation. The importance of considering these factors to promote healthy behaviors was stressed. Discussion This study examined how personal experiences related personal aptitudes and personality traits influence health behaviors and conduct in Spain. It was found that personality traits such as health literacy, self-efficacy, activation, and self-determination can influence the adoption of healthy behaviors. Likewise, the need for control, overthinking, and ambivalence made it impossible. Furthermore, social determinants of health and interpersonal relationships also play an important role. Trial registration ClinicalTrials.gov, NCT04386135. Registered on April 30, 2020